Transformative (h)activism: Breast cancer awareness and the World of Warcraft Running of the Gnomes. - Collister, Lauren B. (Transformative Works & Cultures, 2017)
Players of the massively multiplayer online role-playing game World of Warcraft (WoW) are accustomed to a transformative culture that appropriates off-line events and personas into virtual-world representations inside of the game. Following this culture, players have transformed an off-line event--the Race for the Cure, to benefit breast cancer charities--into an online event called the Running of the Gnomes with parameters and participation properties appropriate for the virtual world. This transformative event is a disruptive form of civil disobedience including elements of hacktivism. Though the event conforms to the game's culture and rules, the mass collective action of the Running of the Gnomes disrupts the player experience by flooding the game's chat boxes with messages about an off-line concern (breast cancer) and also disrupts the game itself by crashing the server through the sheer volume of player participation. This disruption is embraced as an integral part of the event and is one of the primary causes for the event's success as a fundraising activity.